Evaluation On Behavior Change Communication Program Campaign On Hiv And Aids Prevention Among Key Affected Population (Case Study: Information Education Communication, HIV Counseling Test Brochure for Jakarta’s Female Sex Workers) - Novita Sari; Nia Sarinastiti (Atma Jaya Indonesia Catholic University, Jakarta, 2016)
The background of this research is based on the limited qualitative evaluation of HIV prevention campaign conducted by the Indonesia National AIDS Commission. This thesis demonstrates the importance of conducting an evaluation in any communication campaigns. Drawing on P-Process framework and Steps to Behavioral Change, this study examines the impact of HIV Counseling &Testing brochure towards female sex workers in Jakarta province. Five elements are administered to evaluate the expected changes: knowledge, approval, intention, practice, and advocacy. In addition, the element feedback is aimed to accommodate considerations. The research applied qualitative approach, study case method and in-depth interviews towards nine sources to gather information. The result of this research suggests that despite of the positive acceptance from the key affected population, Indonesia National AIDS Commission requires strengthening planning management, development, and testing communication materials.